2018
DOI: 10.1146/annurev-ento-020117-043103
|View full text |Cite
|
Sign up to set email alerts
|

Alien Invasion: Biology of Philornis Flies Highlighting Philornis downsi, an Introduced Parasite of Galápagos Birds

Abstract: The muscid genus Philornis comprises approximately 50 described species of flies, nearly all of which are obligate parasites of nestling birds. Philornis species are native to the Neotropics and widely distributed from Florida to Argentina. Most research on this group has focused on P. downsi, which was introduced to the Galápagos Islands in the late twentieth century. Although Philornis parasitism kills nestlings in several native host species, nowhere do the effects seem more severe than in P. downsi in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 97 publications
(162 reference statements)
0
59
0
4
Order By: Relevance
“…Alternatively, studies have found that larger‐bodied host species can withstand the effects of parasitism of Philornis spp. better than smaller‐bodied host species (Knutie et al, ; McNew & Clayton, ). Smaller‐bodied hosts have a higher surface area to volume ratio and higher metabolic requirements than larger‐bodied hosts (Furness & Speakman, ; Schmidt‐Nielson, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, studies have found that larger‐bodied host species can withstand the effects of parasitism of Philornis spp. better than smaller‐bodied host species (Knutie et al, ; McNew & Clayton, ). Smaller‐bodied hosts have a higher surface area to volume ratio and higher metabolic requirements than larger‐bodied hosts (Furness & Speakman, ; Schmidt‐Nielson, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, swallows sustain fewer parasites per gram of body mass compared to bluebirds, which is likely because swallows resist the parasite with an immunological response. This resistance in swallows could be because they are unable to tolerate similar parasite densities as bluebirds due to their body size because smaller‐bodied hosts probably suffer a higher cost of parasitism (Cardon, Loot, Grenouillet, & Blanchet, ; McNew & Clayton, ). Other studies have also found that bluebirds had higher parasite densities than swallows but the effect of the parasite on the hosts differs based on location and year (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we consider whether ECH occurs in the fly Philornis downsi Dodge & Aitken (Diptera: Muscidae), a neotropical fly with obligate bird ectoparasitic larvae (Dodge & Aitken, 1968;Fessl & Tebbich, 2002;Dudaniec & Kleindorfer, 2006;Fessl et al, 2006). Philornis downsi is native to mainland South America but it has gained notoriety due to the devastating effect that it has had on the endemic passerine fauna of the Gal apagos archipelago where it was first recorded in 1964 (Causton et al, 2006;Fessl et al, 2010Fessl et al, , 2018Kleindorfer et al, 2014;Kleindorfer & Dudaniec, 2016;Koop et al, 2016;McNew & Clayton, 2018). Adult P. downsi females lay their eggs in the nests of passerine birds and on hatching the larvae feed externally and in the nares of the altricial nestlings, rasping at the skin and consuming the blood and lymph from the resulting wounds (Fessl et al, 2006(Fessl et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%